Keputusan Auditor Memberikan Pernyataan Going Concern : Peran Financial Distress, Profitabilitas, Leverage, dan Likuiditas Pada Sektor Energi BEI Periode 2020-2023 - Ajeng Meilana Sari; Artie Arditha Rachman; M. Muhayin A. Sidik (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This research aims to conduct empirical tests regarding the influence of financial distress, profitability, leverage, and liquidity on going concern statement in energy sector companies on the IDX in 2020-2023. This research uses 4 independent variables in the form of financial distress as measured by the Altman z-score, profitability as measured by return on assets, leverage as measured by the debt to asset ratio, and liquidity as measured by the current ratio. The dependent variable is a going concern statement with measurement using a dummy variable. The sampling technique used was a purposive sampling method which was based on certain criteria so that 53 companies were obtained and a total of 212 data. Data testing used logistic regression analysis and IBM SPSS Statistics version 26 software for data processing. The results of this study indicate that the variables of financial distress, profitability, leverage, and liquidity have a simultaneous effect on the going concern statement.